Bacterial pneumonia in children: An integrative review - Santos, Ana Paula Lima Menezes dos; Freitas, Victor Lima de Paiva; Lima, Lucas Alves de Oliveira; Lima, Adeânio Almeida; Oliveira, Átila Jamil; Stefani, Marcio Antônio; Carvalho, Hosana de Nazaré Miranda de; Cordeiro, Leiliane de Carvalho; Silva, Danielly Teixeira Rodrigues da; Menezes, Marco Tulio Soares (Seven Editora, 2024)
The aim of this study was to analyze the risk factors, symptoms, treatment, and diagnoses of bacterial pneumonia in children. The research consisted of an integrative review of the literature, using the Google Scholar and Scielo platforms to search for relevant articles on bacterial pneumonia in children. Strict inclusion criteria were applied, selecting only complete scientific articles available for free online, published between 2019 and 2024. The articles were selected based on their relevance to the topic, analyzing titles, abstracts and complete content. In the end, four articles were chosen and their data were synthesized in an Excel spreadsheet for later analysis. The reviewed studies emphasize bacterial pneumonia as an important public health challenge, especially among children under five years of age, where it is a leading cause of morbidity and mortality. Early identification of signs of severity, such as fever and difficulty breathing, is crucial to guide appropriate treatment, which should be personalized according to the severity of the condition and the specific etiology of the pneumonia. Prevention plays a crucial role in reducing the incidence of the disease, especially vaccination and hygiene measures, while family support is key to mitigating the worsening. However, challenges persist regarding the quality of health care, especially in disadvantaged socioeconomic areas, highlighting the need for investments in infrastructure and technology, as well as research to improve diagnostic and treatment methods. An integrated, multidisciplinary approach is essential to improve clinical outcomes and reduce morbidity and mortality associated with bacterial pneumonia in children and adolescents. DOI:https://doi.org/10.56238/sevened2024.001-052